A mindfulness-based cognitive therapy informed virtual psychiatry trainee wellbeing programme: Development and preliminary feedback. (October 2022) - Chacko, Emme; Vara, Alisha; Cheung, Gary; Naskar, Chandrima; Ramalho, Rodrigo; Bell, Rātahi
Objective: To report the development and feedback on a newly created mindfulness-based cognitive therapy (MBCT) informed virtual wellbeing programme for psychiatry trainees. Methods: Thirteen of the 14 trainees participated in the programme provided feedback via an online questionnaire. Qualitative data was analysed using thematic analysis. Results: Thematic analysis revealed three main themes: timing of the intervention in relation to the COVID-19 pandemic; trainees were connected to the facilitator, their peers and within oneself; and trainees were going through a transformative experience. Discussion: Our findings support including an optional MBCT informed wellbeing programme in psychiatry training programmes. Future research could measure efficacy of this online programme by utilising pre- and post-outcome measures of dispositional mindfulness and stress.